Thalamic GABA+ levels are negatively associated with neuropsychiatric symptoms in patients with insomnia - Dai, Mingyuan; Hong, Huande; Mao, Yumeng; Wang, Rui; Jia, Yanlong; Xu, Dongyuan; Yan, Gen (Frontiers in Human Neuroscience, 2026)
ObjectiveInsomnia is the most common type of sleep disorder; however, the neurobiological causes and correlates of hyperarousal in insomnia remain to be fully determined, and the levels of cerebral metabolites in patients with insomnia remain unclear. This study aimed to quantify changes in cerebral metabolite levels in patients with insomnia and to explore their relationship with fatigue, anxiety, and subjective sleepiness.MethodsTwenty unmedicated patients with insomnia disorder and 21 age- and sex-matched healthy volunteers were included. The concentrations of metabolites including γ-aminobutyric acid (GABA+), glutamate (Glu), glycerophosphocholine (GPC), creatine (Cr), and phosphocreatine (PCr) were obtained by magnetic resonance spectroscopy, and the differences in metabolites between the two groups were compared. Sleep quality, sleepiness, anxiety, and fatigue were assessed using the Pittsburgh Sleep Quality Index (PSQI), Karolinska Sleepiness Scale (KSS), Beck Anxiety Inventory (BAI), and Fatigue Severity Scale (FSS), respectively. Correlations between the changes in GABA+, Glu, and GPC levels and the PSQI, KSS, FSS, and BAI scores were evaluated in patients with insomnia.ResultsGABA+ levels were significantly lower in patients with insomnia than in healthy controls (p = 0.027), whereas GPC and Cr+PCr levels were significantly higher (p < 0.001 and p = 0.003, respectively). However, Glu levels were comparable between the groups (p = 0.962). Furthermore, GABA+ levels were significantly negatively correlated with FSS (r = −0.656, p = 0.003) and BAI (r = −0.467, p = 0.038) scores; a trend-level negative association with KSS was also observed (r = −0.419, p = 0.066).ConclusionOur results revealed alterations in the levels of GABA+ and GPC in the thalamus of patients with insomnia. These findings provide objective neurochemical evidence for the pathophysiological mechanisms of insomnia.